The Reflection of Chinese Hui Muslim Life in Huo Da’s Novel: Funeral of A Muslim (穆斯林的葬礼) - Ilmi, Malikah Kautsar; Soronika, Razia Sultana (Universitas Al Azhar Indonesia, 2026)
This study explores the reflection of Hui Muslim life and Islamic religious practices in Huo Da’s novel Funeral of a Muslim (1988), an outstanding work in Modern Chinese literature that centers on minority religious experience in China. Set within the historical and social transformations of twentieth-century China, the novel traces three generations of a Hui Muslim family in Beijing and offers a rare literary portrayal of Islamic life in a predominantly Han cultural context. Employing a Qualitative Literary Methodology through close reading, this research analyzes selected narrative passages and dialogues from the English translation of the book to examine depictions of Islamic rituals, including greetings, ablution, prayer, marriage and funerary practices. This study finds that Funeral of a Muslim not only contributes to Chinese literary fiction through its depiction of ethnic minority religious practices, but also reveals that Hui identity is constructed as a dynamic process of dialogical interaction between self-perception and sociopolitical structures.Keywords - Chinese Hui, Contemporary Chinese Literature, Hui Muslim Life, Religious Practices.